Increase of glutamate in satellite glial cells of the trigeminal ganglion in a rat model of craniofacial neuropathic pain - Cho, Yi Sul; Mah, Won; Youn, Dong Ho; Kim, Yu Shin; Ko, Hyoung-Gon; Bae, Jin Young; Kim, Yun Sook; Bae, Yong Chul (Frontiers in Neuroanatomy, 2023)
Introduction Satellite glial cells (SGCs) that envelop the cell bodies of neurons in sensory ganglia have been shown to both release glutamate, and be activated by glutamate in the context of nociceptive signaling. However, little is known about the subpopulations of SGCs that are activated following nerve injury and whether glutamate mechanisms in the SGCs are involved in the pathologic pain. Methods To address this issue, we used light and electron microscopic immunohistochemistry to examine the change in the glutamate levels in the SGCs and the structural relationship between neighboring neurons in the trigeminal ganglion (TG) in a rat model of craniofacial neuropathic pain, CCI-ION. Results Administration of ionomycin, ATP and Bz-ATP induced an increase of extracellular glutamate concentration in cultured trigeminal SGCs, indicating a release of glutamate from SGCs. The level of glutamate immunostaining in the SGCs that envelop neurons of all sizes in the TG was significantly higher in rats with CCI-ION than in control rats, suggesting that SGCs enveloping nociceptive as well as non-nociceptive mechanosensitive neurons are activated following nerve injury, and that the glutamate release from SGCs increases in pathologic pain state. Close appositions between substance-P (SP)-immunopositive (+) or calcitonin gene-related peptide (CGRP)+, likely nociceptive neurons, between Piezo1+, likely non-nociceptive, mechanosensitive neurons and SP+ or CGRP+ neurons, and between SGCs of neighboring neurons were frequently observed. Discussion These findings suggest that glutamate in the trigeminal SGCs that envelop all types of neurons may play a role in the mechanisms of neuropathic pain, possibly via paracrine signaling.